2022
DOI: 10.3390/healthcare10102109
|View full text |Cite
|
Sign up to set email alerts
|

Clothes Make the Man—What Impact Does the Dress of Interprofessional Teams Have on Patients?

Abstract: Physicians’ attire seems to play an important role in the success of patient treatment. The classic doctor’s white coat initiates a strong signal to the patient and can have a determining effect on a successful doctor–patient relationship. In a quantitative online questionnaire study comprising 52 questions, participants were shown four photos of an interprofessional German family medicine team in varying attire. One important study feature relating to the ongoing coronavirus pandemic was that the team was por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…More than 90% of our respondents strongly agreed or agreed on the importance of anesthesiologist attire in building trust, which was consistent with previous studies focused on physicians in other specialties. 22 Unlike the other specialties, anesthesiologists do not have many opportunities to communicate with their patients. Thus, it is more important for them to dress appropriately and leave good impressions within the limited time of preoperative visit.…”
Section: Discussionmentioning
confidence: 99%
“…More than 90% of our respondents strongly agreed or agreed on the importance of anesthesiologist attire in building trust, which was consistent with previous studies focused on physicians in other specialties. 22 Unlike the other specialties, anesthesiologists do not have many opportunities to communicate with their patients. Thus, it is more important for them to dress appropriately and leave good impressions within the limited time of preoperative visit.…”
Section: Discussionmentioning
confidence: 99%
“…However, Kowalewska et al noticed that in younger age groups, having tattoos is most often perceived as a form of decoration (54%), while older people considered them to be an uncritical following of fashion (47%) [20]. In turn, studies by Sotgiu et al and Roehrens et al showed that older patients significantly more often prefer the classic appearance of doctors than younger ones, who were more likely to follow current fashion and trends [21,22]. The reason for this situation may be the fact that older genera-tions, over time, become more and more conservative and reluctant to change [23].…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore recommended to adopt the attire according to the objective sought and the patient group targeted. [46] 5. CONCLUSION…”
Section: Discussionmentioning
confidence: 99%